9A.06: IMPACT OF METABOLIC, HEMODYNAMIC AND INFLAMMATORY FACTORS ON TARGET ORGAN DAMAGE IN HEALTHY SUBJECTS. (June 2015) - Blicher, M.; Kruger, R.; Olesen, T.; Greve, S.; Hansen, T.; Olsen, M.H.
Abstract : Objective: We wanted to test the impact of metabolic, hemodynamic and inflammatory factors on target organ damage (TOD) defined as cardiac hypertrophy, atherosclerosis, arterioclerosis and microvascular damage. Design and method: In a population based cohort study of 2115 healthy subjects (1049 male 1066 female) with a mean age of 53.1 ± 10.5 without known diabetes or cardiovascular disease we measured fasting plasma glucose (FPG), serum insulin, lipid profile, soluble urokinase receptor (suPAR), c-reactive protein (CRP), urine albumin/creatinine ratio (UACR), 24-hour ambulatory systolic (24hSBP) and diastolic blood pressure (24hDBP), left ventricular mass index (LVMI) by M-mode echocardiography, carotid plaques (CP) by carotid ultra sound and carotid-femoral pulse wave velocity (PWV). To establish best model for association of LVMI, CP, PWV and UACR we used multiple linear regression analysis starting with inclusion of all variables without co-linearity taking away one by one non-significant variables. Results: Cardiac hypertrophy assessed by LVMI was primarily associated with gender (β = 0.37), 24hSBP (β = 0.26) and HR (β = -0.15). Insulin resistance (IR) and inflammation only had minor albeit significant impact on LVMI assessed by HOMA (β = 0.09) and CRP (β = 0.05). Atherosclerosis assessed by CP was primarily associated to age (β = 0.31), 24hSBP (β = 0.13) and smoking (β = 0.13). Arteriosclerosis indicated by PWV was primarily associated to age (β = 0.39), 24hSBP (β=0.31), gender (β = 0.14) and HR (β = 0.15). Additionally, FPG (β = 0.04), total cholesterol/high density lipoprotein ratio (TC/HDL) (β = 0.04) and CRP (β = 0.03) had positive independent impact on PWV. Microvascular damage assessed by UACR was primarily associated to gender (β = -0.16), 24hSBP (β = 0.09) suPAR (β = 0.09), smoking (β = 0.05) and age (β=0.05). Conclusions: We conclude that 24hSBP were independently associated to cardiac hypertrophy, arteriosclerosis, atherosclerosis as well as microvascular damage, whereas IR and inflammation were only weakly, independently associated to hypertrophy, arteriosclerosis and microvascular damage in healthy subjects.